Analisis Kebutuhan Air Dan Finansial Tanaman Krisan (Chrysanthemum Sp.) Dengan Metode Guludan Dan Pot - I Gede Ngurah Salpatira Widayana; I Wayan Tika; I Made Anom S. Wijaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
Chrysanthemum flower (Chrysanthemum sp.) are one of the ornamental plants produced as cut flowers. Chrysanthemum cultivation usually uses the bund method, but nowadays chrysanthemum cultivation has develoved using the pot method. The development of two methods of cultivation resulted in differences in the plant water requirements and financial in each methods. Therefore it is necessary to conduct research to analyze the plant water requirement and the financial feasibility of each method. The purpose of this research are to : (1) determine the difference of water requirement level on the cultivation of chrysanthemum flower using the method of bund and pot, and (2) analyze the finance feasibility on cultivation of chrysanthemum flower with both methods. The treatment of this research are : cultivation of chrysanthemum flower with bund method and cultivation of chrysanthemum flower with pot method. In each method analyzed plant water requirements (ETc) and financial feasibility. The analysis of financial feasibility used in this research is NPV, IRR and BCR. Total requirement of chrysanthemum flower water with bund and pot method are 1056,72 ml/plant and 866,64 ml/plant, while the average daily water requirement is 19,57 ml/day, and 16,05 ml/day. The financial feasibility result of this are NPV on bund method as much as Rp.5.687.537,35 is smaller than the pot method which is worth Rp. 12.627.709,99. IRR from the bund method with percentage 15% smaller than pot method with the percentage of 18%. The BCR analysis of the bund method yields 1.51 which is smaller than the pot method which yields 1.63. although both methods of chrysanthemum flower cultivation are said to be feasible, but the pot method is more advantageous than the method of bunds in financial terms.